Empowering Students with the “Ten Core Competencies”: A Practical Exploration of Study Tour Curriculum at Tiqiang Road Junior High - 潘雪莉; 刘 虎 (Education Research on Study Tours and Practice, 2025)
Anchored in the educational philosophy of "Universal Love and Diligent Learning, Physical Fitness and Inner Strength," Tiqiang Road Junior High School in Nanning has developed a study tour curriculum guided by the ’Ten Core Competencies’ framework. The curriculum is implemented through grade-specific progressive pathways: Grade 7 ("Self-Knowledge") focuses on cultural immersion in students’ hometown; Grade 8 ("Social Integration") deepens comprehensive practice via a football season project; and Grade 9 ("Future Planning") connects with career exploration. Innovative interdisciplinary learning tools (e.g., the "Museum Challenge Card" and "Football Fan Quiz") are employed, alongside the integration of a three-tiered resource chain ("Hometown — Nation — World"). This approach effectively addresses common challenges in junior high study tours, such as vague objectives, fragmented implementation, and subject compartmentalization. Significant outcomes include: a marked increase in hometown cultural awareness among Grade 7 students (from 62% to 91%), a 15% improvement in the physical fitness pass rate for Grade 8, and enhanced social responsibility and planning abilities among Grade 9 students. This model has not only forged a municipally recognized moral education brand but also established a replicable operational paradigm of "tiered goal-setting — resource integration — tool innovation — evaluation-driven improvement", offering a practical solution for effectively cultivating core competencies through study tours at the junior high level.